PENGGUNAAN MODEL PEMBELAJARAN GROUP INVESTIGATION UNTUK MENCAPAI KOMPETENSI BELAJAR BIOLOGI MATERI SISTEM PEREDARAN DARAH MANUSIA PADA SISWA KELAS VIII SMP St. THERESIA LANGGUR – MALUKU TENGGARA - Magdalena Sumanik (BIOPENDIX, 2015)
Background: This study aimed to determine how to use learning model group investigation in biology learning material human circulatory system in class VIII SMP St. Theresia Langgur Southeast Maluku. Methods: This study used quantitative descriptive method by providing an overview of the achievement of learning outcomes biological material on the human circulatory system. The way of data collection is done through initial and final test and observation during the learning process. Data analysis techniques with descriptive analysis based on the results of the pre and posttest. Results: The results showed that there are progress learning outcomes achieved by students after learning by using a model group investigation. The students were on a pre-test value is taken KKM, after corrective action in learning the value rises past the KKM. Conclusions: The use of learning model group investigation in biology learning material human circulatory system in class VIII SMP St. Theresia Langgur Southeast Maluku experienced a significant increase.